PARTIAL USE LICENSE - Desarrollo Rural, Cuadernos de (2015)
By submitting items for evaluation (a) author (s) be in agreement (s) to transfer (n) the copyright to the Cuadernos de Desarrollo Rural, for publication in print or electronic format and use partially enclosed license is signed.